2001
DOI: 10.1038/sj.neo.7900173
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Lengths and Telomerase Activity in Dog Tissues: A Potential Model System to Study Human Telomere and Telomerase Biology

Abstract: Studies on telomere and telomerase biology are fundamental to the understanding of aging and age-related diseases such as cancer. However, human studies have been hindered by differences in telomere biology between humans and the classical murine animal model system. In this paper, we describe basic studies of telomere length and telomerase activity in canine normal and neoplastic tissues and propose the dog as an alternative model system. Briefly, telomere lengths were measured in normal canine peripheral blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
102
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(114 citation statements)
references
References 36 publications
8
102
0
4
Order By: Relevance
“…By contrast, we did find a significant negative correlation between age and telomere length in Chihuahua dogs (n=89). A shortening of telomeres with cell replications of in vitro canine fibroblasts has been detected [22] , and Fick et al [21] showed a connection between telomere loss with age in 15 dog breeds (n=175), similar to our results. Furthermore, Fick et al [21] reported that different dog breeds varied in telomere length, which contributed to average lifespan.…”
Section: Discussionsupporting
confidence: 81%
“…By contrast, we did find a significant negative correlation between age and telomere length in Chihuahua dogs (n=89). A shortening of telomeres with cell replications of in vitro canine fibroblasts has been detected [22] , and Fick et al [21] showed a connection between telomere loss with age in 15 dog breeds (n=175), similar to our results. Furthermore, Fick et al [21] reported that different dog breeds varied in telomere length, which contributed to average lifespan.…”
Section: Discussionsupporting
confidence: 81%
“…This activity protects the integrity of chromosomes from digestion by exonucleases, fusion to the neighboring chromosomes and occurring the chromosomal defects [29,30] . Possible relation between carcinogenesis and telomere dysfunctions was reported [31,32] .…”
Section: Discussionmentioning
confidence: 99%
“…Dogs develop spontaneous tumors that display behavior and histo-pathological characteristics to human tumors [6][7][8]. For example, in dogs, studying about the role of inhibition of telomere size shortening plays in cell immortalization and proliferation is relevant, because dog chromosomal telomeres closely resemble human telomeres than murine telomeres [9]. Among the practical benefits of clinical investigation of cancer in dogs is the fact that due to their shorter life span, clinical intervention is easily studied over a condensed period of time.…”
Section: The Reason Behind Dogmentioning
confidence: 99%